Subarachnoid meloxicam does not inhibit the mechanical hypernociception on carrageenan test in rats - Lanucha Fidelis da Luz Moura (Revista Brasileira de Anestesiologia, 2015)
BACKGROUND AND OBJECTIVE: Evaluate the antinociceptive effects of subarachnoid meloxicam on the mechanical hypernociception induced by carrageenan in rats. METHODS: Randomized controlled trial. Eighteen adult male Wistar rats underwent a cannula implantation into the subarachnoid space and were randomly divided into two groups: Group I received saline solution 5 µL, while Group II received meloxicam 30 mg. The mechanical hypernociception was induced by intraplantar injection of carrageenan and evaluated using a digital analgesy meter every 30 min during a 4-h period. The results were recorded as the Δ withdrawal threshold (in g), calculated by subtracting the measurement value after treatment from baseline. RESULTS: The Δ withdrawal threshold mean values were lower in the group of patients treated with meloxicam over all time points between 45 and 165 min, however, there was no statistical significance (p = 0.835) for this difference. CONCLUSION: Subarachnoid meloxicam at a dose of 30 µg animal-1 did not suppress the mechanical hypernociception in a model of inflammatory pain induced by intraplantar administration of carrageenan in rats. The data suggest that other dosages should be investigated the drug effect is discarded.